Selection index for simultaneously improving fruit production components of assai palm - Teixeira, Davi Henrique Lima; Oliveira, Maria do Socorro Padilha de; Gonçalves, Flávia Maria Avelar; Nunes, José Airton Rodrigues (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to determine the most appropriate strategy to simultaneously increase fruit production components of assai palm (Euterpe oleracea). An experiment with 25 half‑sib progenies was carried out in the county of Santa Isabel, PA, Brazil, using a randomized complete block design with four replicates and five plants per plot. The Smith & Hazel, Williams, and Mulamba & Mock’s selection indexes were applied in three selective strategies. The coefficients of genetic variation, heritability, the ratio between the genetic correlation of the trait under selection and fruit yield, and the sum of all genetic correlations between the traits that comprise the index and fruit yield were used as economic weights. Weighting of the correlation ratio allowed the selection indexes to discriminate the best progenies in the different selection strategies evaluated. Simultaneous selection by the Mulamba & Mock index, as to the number of fruiting months, number of bunches harvested, fruit yield, and number of rachilles per bunch, robustly estimates genetic gains.